2012
DOI: 10.3892/ijo.2012.1710
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule inhibition causes epidermal growth factor receptor inactivation in oesophageal cancer cells

Abstract: Abstract. Drugs that interfere with microtubule function can prevent cells from mitosis and may cause cell cycle arrest or apoptosis. Various microtubule targeting agents, both stabilizers and inhibitors, are used in a clinical setting to treat cancer. In the current study, we investigated the sensitivity of oesophageal cancer cells to different microtubule targeting agents. The current study demonstrated that different microtubule targeting agents disrupted the microtubule network and inhibited survival of oe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…We have previously shown that the disruption of the microtubule system by PPT or vincristine causes the dephosphorylation and degradation of the EGFR (26). We obtained similar results in this work using PPP (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We have previously shown that the disruption of the microtubule system by PPT or vincristine causes the dephosphorylation and degradation of the EGFR (26). We obtained similar results in this work using PPP (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…EGFR but not IGF-IR (26). Therefore, we investigated whether PPP had similar effects on EGFR, which was expressed in all of the ESCC cell lines in the panel (not shown).…”
Section: Ppp Inhibits Egfr and Decreases Downstream Signaling From Tymentioning
confidence: 99%
“…Addition of Docetaxel, PPT and Vincristine inhibited the phosphorylated form of Akt, while PPT and Vincristine resulted in decreased phosphorylation of Erk. The effects of microtubule disruption on EGFR activity were diminished when a phosphatase inhibitor was added . These results effectively link the microtubule network to EGFR activity .…”
Section: Discussionmentioning
confidence: 74%
“…We also report accelerated entry into catagen and completion of the first hair cycle in mice with genetic deletion of Stmn1, suggesting that the deregulation of microtubule dynamics in follicular keratinocytes is involved in catagen. Wu and colleagues using microtubule‐destabilizing agents in oesophageal carcinoma lines established the relationship between EGFR and the microtubule network . They report a decrease in EGFR phosphorylation following treatment with taxol and PPT.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that Tau is a key inhibitor of wild-type EGFR signaling in gliomas. Accordingly, drugs that interfere with microtubule function have been associated with EGFR inactivation in other cancers (43), as they seem to alter endocytic trafficking (11). Moreover, it has been shown that microtubule acetylation, which is promoted by Tau function (16), promotes the degradation of EGFR through changes in the microtubule-dependent endocytic trafficking (17).…”
Section: Tau Expression Is a Surrogate Marker Of The Less Aggressive mentioning
confidence: 99%